The Construction of Smoking Addiction Scale in Adolescents - Dwiki Nardian Putra; Sofiyyatuw Wakhidah; Afifah Tiara Briliani; Afifah Dwi Pramesti; Anas Adha Saputra; Icha Putri Kusuma,; Aftina Nurul Husna (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose and benefits of this research is to develop an instrument used to measurepsychological attributes and it is hoped that this scale can be used for further research.Addiction is a form of psychological dependence between a person and a stimulus, whichis usually not always an object or substance. There are two aspects in this scale, namelythe psychological aspect and the physical aspect. The stages of Scale Development startfrom setting the measurement objectives, confirming the measuring area, andpsychometric testing. Furthermore, item writing includes the selection of the stimulusformat, the selection of the response format, the writing of items: rules, item testing. Thenthe psychometric test. The subjects of this study consisted of 53 male adolescentrespondents who smoked and were aged 13-19 years old, domiciled in the City/Regency ofMagelang. The way to collect this research data is through an online survey. The resultsof the content validity test by referring to the Aiken's V formula with a V value of 0.9, thereare 9 items that are good because the results have reached 0.9. And as many as 20 itemsthat must be revised because V is close to 0.9. Based on the results of the reliability test,Cronbach's alpha was 0.957, which means the item is very good. The smoking addictionscale in adolescents was developed and produced 60 items, then a reliability test wascarried out using SPSS statistic 22 software so that the final result of this scale was thatthere were 20 items that could represent the construct being measured.